Variabilities of ground motion in 2023 M w 7.8 Pazarcık earthquake in Turkey and 2008 M w 7.9 Wenchuan earthquake in China - Peibin Xu; Xingguo Liu; Lin Li (Scientific Reports)
Abstract Both the 2023 M w 7.8 Pazarcık earthquake (strike-slip fault) in Turkey, and the 2008 M w 7.9 Wenchuan earthquake (reverse-slip fault) in China occurred on the Eurasian seismic belt, with comparable moment magnitudes. This study investigates the ground-motion characteristics of both earthquakes, using ground motion intensity measures (IMs), including peak ground accelerations (PGA), peak ground velocities (PGV), pseudospectral accelerations (PSAs) at T = 0.2–5.0 s, 5–95% significant duration, Arias intensity (I a) and Newmark displacement. The Pazarcık earthquake shows negative between-event residuals (δB e ) at T < 0.2 s and positive δB e at T > 0.2 s, indicating source effects in BSSA14 model over- and under- prediction respectively. The Wenchuan earthquake, however, displays uniformly positive δB e (all T), revealing source effects underprediction. Larger δB e values were observed at long/intermediate period (T > 0.2 s) for Pazarcık earthquake, but smaller at short period (T < 0.2 s), compared with Wenchuan event. Such period-dependent differences of ground motions between the two events may be attributable to fault types and Fault slip distribution at depth. Within the structure natural frequency range (0.5–1.5 Hz) of the primary buildings in both earthquakes affected area, more recordings for Pazarcık earthquake exceeded PGA and PGV thresholds from Chinese intensity scale IX, implying that its ground motion has greater impact on structures damage. The Wenchuan earthquake exhibits larger Arias intensity and greater deviations from predicted models compared to the Pazarcık event, reflecting its ground motion richer high-frequency content. These differences in Arias intensity may be attributable to different fault types and stress drop (Δσ) between the two earthquakes. At similar distances, Wenchuan earthquake exhibits longer 5–95% significant duration than Pazarcık’s. The result may be attributed to their different fault styles, rupture directivity, and rupture mechanisms. Both earthquakes produced Newmark displacements values exceeding 2 cm at multiple sites, indicating significant landslide hazards in their respective affected regions.